FREE VIBRATION ANALYSIS OF SPATIAL FRAMES WITH VARIOUS BOUNDARY CONDITIONS - Žugić, Ljiljana; Brčić, Stanko; Gropčević, Špiro (Journal of Applied Engineering Science, 2016)
Free vibration analysis of the spatial frames consisting of 3D beam elements is presented in the paper, using the consistent mass matrix, as implemented in the code ALIN, which is written in C++. The values of circular frequencies for the spatial simply supported and clamped-clamped beam, obtained by using ALIN, are compared with the exact solutions and the solutions obtained by using the code TOWER. In order to obtain better, more exact, results, it is necessary to discretize the frame into more finite elements. As opposed to TOWER, which is using the lumped mass matrix, the code ALIN is using the consistent mass matrix, thus allowing wider discretization, into smaller number of finite elements, then in the case of TOWER.